ASSESSORIA PEDAGÓGICA UNIVERSITÁRIA NO CONTEXTO DA UNIVERSIDADE NOVA: MAPEAMENTO E REFLEXÕES - Xavier, Amanda Rezende Costa (2020)
This paper introduces the University Pedagogical Advisory by mapping it at the Universidade Nova context, that is, identifying the institutional agents that play role as Advisory Pedagogical in a set of Brazilian federal universities that offer Interdisciplinary Bachelor. The mapping method relies on documental research and documental analysis procedures. Composing a finalized doctoral research in education (XAVIER, 2019), in the field of University Pedagogy, the mapping ranger from 2016 to 2019, which was sufficient to observe changes in the universities researched. Results point towards the increase in initiatives to establish dedicated sectors to teaching formation into the Universities, although there is still a long way until these could be legitimated as University Pedagogical Advisory. Results also showed that despite the effort to establish such services, there are very heterogeneous levels of commitment to this movement. Therefore, it was found into the university set, some in which the consolidation of sectors responsible for pedagogical advice are in advanced level, while in some others there is not even plan to establish such services. Such results emphasize the need to establish the University Pedagogical Advisory services as a University formal goal.